Application of swallowtail catastrophe theory to transient stability assessment of multi-machine power system - Bugis, Ismadi; Hassen Kareem, Maithem (Little Lion Scientific Islamabad Pakistan, 2013)
Transient stability analysis is an important part of power planning and operation. For large power systems, such analysis is very demanding in computation time. On-line transient stability assessment will be necessary for secure and reliable operation of power systems in the near future because systems are operated close to their maximum limits. In this manuscript swallowtail catastrophe is used to determine the transient stability regions. The bifurcation set represents the transient stability region in terms of the power system transient parameters bounded by the transient stability limits. The transient stability regions determined are valid for any changes in loading conditions and fault location. The system modeling is generalized such that the analysis could handle either one or any number of critical machines. This generalized model is then tested on numerical examples of multi-machine power system (Cigre seven machine systems) shown very good agreement with the time solution in the practical range of first swing stability analysis. The method presented fulfills all requirements for on-line assessment of transient stability of power system